The preschool strengths inventory: development and validation - Owens, Rhea L.; Patterson, Meagan M.; Multon, Karen D. (Frontiers in Psychology, 2025)
There is a lack of research on young children’s strengths, likely in part due to limited tools available to identify individual strengths in early childhood. To help address this gap and provide a brief measure for parents, researchers, and practitioners, the 37-item Preschool Strengths Inventory (PSI) was developed. First, focus groups with parents were conducted to identify strengths in early childhood. Based on the results of the focus groups and a review of the research, items were developed, reviewed by experts, and tested through exploratory and confirmatory factor analysis. The five factors identified were: Dynamic, Dependable, Caring, Inspiring, and Organized. Lastly, validity was tested and established with measures of personality traits and social skills, and the PSI’s test–retest reliability was examined. Results provide support for the content structure, reliability, and validity of the PSI. The PSI can provide the ability to study strengths beginning early in life and provide a foundation to develop strengths-focused interventions.